World cinema and the essay film : transnational perspectives on a global practice - Hollweg, Brenda; Krstić, Igor (Edinburgh University Press, 2019)
World Cinema and the Essay Film examines the ways in which essay film practices are deployed by non-Western filmmakers in specific local and national contexts, in an interconnected world.